MENINGKATKAN PRESTASI BELAJAR SISWA MELALUI PEMBERIAN MOTIVASI BELAJAR - S, Nur Eni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This journal describes efforts to improve student learning achievement in lessons through motivation. This study uses a test method and classroom action observation. Data analysis using descriptive analysis. The research subject was a class VI student at SD Rejeki Elementary School. The success obtained during this third cycle is as follows, the activities of students in PBM are very active due to the giving of learning motivation. And the average student's daily test score (evaluation) increased from 5.79 before the action (T0) to 6,097 cycle one (T1), 7,33 Cycle two (T2), and 8,097 cycle three (T3). Thus, it has been proven that the learning approach with the provision of learning motivation can improve the PBM process and student learning achievement.